2014
DOI: 10.1111/rge.12026
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Characteristics of Apatite in HeavyREE‐rich Deep‐Sea Mud fromMinami‐Torishima Area, SoutheasternJapan

Abstract: We have conducted geochemical and mineralogical investigations of the rare earth and yttrium (REY)-rich mud from the Minami-Torishima area in the Pacific in order to clarify the concentration of REY and their host-phase in the mud. X-ray diffraction analysis shows that the mud is mainly composed of phillipsite, fluorapatite, quartz, albite, illite and montmorillonite. Whole-rock CaO, P2O5 and total REY contents of the mud are positively correlated. Relative abundance of apatite is also positively correlated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 24 publications
7
81
0
1
Order By: Relevance
“…Based on the mole fractions of Ca and P, the regression-line slope is 0.48. This value is smaller than the ideal stoichiometry of Ca and P fractions in the Ca-phosphate phase (apatite) (5:3 = 0.6), but is similar to that in the REE-rich deep-sea mud near the Minami-Torishima Island (Kon et al, 2014). Moreover, the Ca-and P-rich parts of the crusts sometimes appear white or pale brownish color, indicating that the amount of apatite increases with depth in the crust.…”
Section: Major Element Composition Of the Takuyo Daigo Fe-mn Crustsmentioning
confidence: 69%
See 1 more Smart Citation
“…Based on the mole fractions of Ca and P, the regression-line slope is 0.48. This value is smaller than the ideal stoichiometry of Ca and P fractions in the Ca-phosphate phase (apatite) (5:3 = 0.6), but is similar to that in the REE-rich deep-sea mud near the Minami-Torishima Island (Kon et al, 2014). Moreover, the Ca-and P-rich parts of the crusts sometimes appear white or pale brownish color, indicating that the amount of apatite increases with depth in the crust.…”
Section: Major Element Composition Of the Takuyo Daigo Fe-mn Crustsmentioning
confidence: 69%
“…8b). A laser ablation ICP-MS analysis of apatite in the REE-rich deep-sea mud near Minami-Torishima Island has shown that apatite has a HREE-enriched pattern with a conspicuous negative Ce anomaly, similar to modern seawater (Kon et al, 2014). Thus, the slightly HREE-enriched patterns in samples with more than 0.5 wt% P can be produced by a mixture of non-phosphatized Fe-Mn crust and apatite.…”
Section: Trace Element Compositions Of the Takuyo Daigo Fe-mn Crustsmentioning
confidence: 98%
“…We identified the host phase of REEs based on chemical leaching technique previously employed by Toyoda and Masuda (1991) and Takebe (2005). In addition, we have obtained the REE patterns of Mn 4+ oxides and apatite by measuring REE contents of each phase directly using laser ablation inductively coupled plasma-mass spectrometry (LA-ICP-MS) as reported by Kon et al (2014). As for chemical species that can be effected by the early diagenesis, the oxidation state of Ce related to the appearance of Ce anomaly in sediments was determined by X-ray absorption near-edge structure (XANES) at the Ce L III -edge (Takahashi et al, 2000a), coupled with the speciation of Mn and Fe by K-edge XANES (Fukukawa et al, 2004;Takahashi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The apatite in the deep-sea mud around Minami-Torishima Island is enriched in REE, especially HREE (Table 5), and has characteristics similar to those of fish debris [16]. Thus, the origin of the deep-sea mud apatite is completely different from those in IOA deposits, and is characterized by relatively low contents of radioactive elements (Th: 140 ppm, U : 21 ppm) [16].…”
Section: Heavy Rare Earth Mineralization In Submarine Mudmentioning
confidence: 99%